Fração P1G10 do látex de Vasconcellea cundinamarcensis: atividade antitrombótica in vivo e anticoagulante/antiagregante plaquetário in vitro - Rogerio Pereira Bilheiro (2012)
Previous studies have suggested that P1G10, a cistein protease obtained from the latex of Vasconcellea cundinamarcensis may have an effect on the hemostatic system, given that signs of haemorrage were found in Wistar rats during toxicological assays. In addition, the literature describes not only an important antithrombotic effect of other cistein proteases in vivo, but also their capacity to inhibit coagulation and platelet aggregation in vitro. Based on this, this study aimed at evaluating the effect of P1G10 in a light/dye model of thrombotic obstruction in the ear microvessels of hairless mice, as well as to propose a coherent pharmacological mechanism for such effect. For the thrombotic obstruction, 0.15 mL of FITC-dextran (6%) was injected in the tail vessel and the ear microvessels were subjected to continuous blue mercury light exposure on an epi-illumination microscope. P1G10 (2.5, 5.0 or 7.5 mg/kg), P1G10-IAA (5.0 mg/kg) or saline were injected s.c. 25 min before the thrombus induction. While P1G10-IAA showed no significant antithrombotic effect; at the dose of 2.5 mg/kg an importat prolongation of the time for a stable thrombus formation was observed, whereas at 5.0 and 7.5 mg/kg, no stable thrombotic obstruction of the vessels was observed in the time elapsed for experimental analysis (20 min). In in vitro assays, P1G10, at the final concentrations of 0.5 g/L and 1.0 g/L, significantly inhibited platelet aggregation in PRP. In coagulation assays, a significant prolongation in the coagulation time was observed by PT at the final concentration of 1.0 g/L, whereas no coagulation was observed at 2.0 g/L. By APTT, P1G10 significantly prolonged the coagulation time at 0.5 and 1.0 g/L, and no coagulation was observed at 2.0 g/L. In the TT assay, an important prolongation in the coagulation time was observed at 0.25 g/L, and no coagulation was obseved at 0.5 g/L. When plasma fibrinogen concentration was measured in vitro after incubation with P1G10, there was a significant decrease in fibrinogen levels at 0.05 g/L, which then became indetectable at the 0.5 g/L. In the fibrin plate assay, P1G10 showed fibrinolytic effect at 1.0 g. Based on this results, we suggest that P1G10 has antithrombotic activity in vivo and antiplatelet / anticoagulant activity in vitro.